Dissecting the differentiation process of the preplacodal ectoderm in zebrafish. Issue 10 (19th July 2014) - Yao, Di; Zhao, Feng; Wu, Ying; Wang, Jialiang; Dong, Wei; Zhao, Jue; Zhu, Zuoyan; Liu, Dong; Mansour, Suzanne L.; Ornitz, David M.
<x xml:space="preserve">Abstract</x> Background: The preplacodal region (PPR) is a region of specialized ectoderm at the border of neural and nonneural ectoderm (NNE). Coordinated Bmp, Fgf, and Wnt signals are known to drive PPR development; however, the underlying mechanism is unknown. Results: We identified key components involved in PPR differentiation. The mesoderm/marginal Wnts at the early gastrula stage trigger differentiation by allowing the adjacent NNE border cells to start adopting caudal PPR fates; otherwise, the development of caudal PPR identity is hindered due to the persistent presence of gata3 mRNA. The caudal PPR fate dominates when foxi1 expression is enhanced at the late gastrula stage, and depleting Foxi1 after 6 hours postfertilization (hpf) reduces the otic‐epibranchial placodal domain. When the Gata3 level is manipulated at the fertilized egg stage or near 6 hpf, the lens is always affected. In establishing PPR polarity, both Gata3 and Foxi1 inhibit Bmp signaling, whereas Foxi1 inhibits, but Gata3 enhances, Fgf sensitivity of the PPR cells. Conclusions: Our study reveals that in zebrafish, (1) the PPR at the shield stage may enter a developmental state when the PPR cells preferentially adopt a particular placodal fate and (2) a network of genetically linked factors, including Wnt/beta‐catenin, Fgfr, Bmp, Gata3, and Foxi1, direct the process of PPR differentiation. Developmental Dynamics 243:1338–1351, 2014. © 2014 Wiley Periodicals, Inc.